Can Women Keep Managerial Positions in Saudi Arabia? The Impact of Glass Ceiling and Leadership Empowerment on Work-Life Balance - Alshammari, Hammad (iRASD Journal of Management, 2023)
This study investigates the factors that impact female workers maintaining leading positions. The primary purpose of the search is to study the effect of the glass ceiling and leadership empowerment on women's work-life balance in the private sector in Saudi Arabia. A survey research design was employed, and a cross-sectional approach to data collection was used to achieve the primary objectives. Thus, data were collected from 54 selected female executives working in private enterprises in Saudi Arabia. Closed-ended questions-based Likert scales were employed to gather data from the research participants. The study uses Multiple regression to analyze the data collected using SPSS. Consequently, it was found that the empowerment of female leadership has a significant influence on the work-life balance of female leaders in the private sector of Saudi Arabia. On the other hand, the glass ceiling was not found to significantly impact the participants' work-life balance. Finally, it was concluded that attempts should be made to support female leaders as this will positively affect their work-life balance and consequently leads to better performance.